Paham Teologi dan Visi Kebangsaan Masyarakat Lombok - Asnawi Asnawi (Universitas Islam Negeri Mataram, 2009)
The Dutch colonialism over Lombok Island in 1894 caused severe sufferings. Under their control, Lombok people were oppressed and suffered. Theology and tariqat practices built anti-imperialist spirit within Muslim society to the infidel imperialists. Consequently, Muslim leaders like Tuan Guru who were also tharîqah teachers aroused the war for the sake of Allah. Tuan Guru propagated Islamic teachings so that Islam then became an ideological base for fights against the infidel Dutch. This urged the Dutch to chase Muslim leaders and look for information about tharîqah movements. Such repressive efforts led them to rebel. Lombok people’s fanaticism to Islam awakened anti-imperialist spirit and movements. Considering Lombok people’s fights against Gel-Gel King of Bali and the Dutch, Islamic spirit was an intrinsic part of the struggle against colonialism. It was clear that the Islamic spirit of independence moved them to struggle.